Two years in review: National food systems certification next steps - Kaley Hohenshell; Courtney Long (Urban Food Systems Symposium, 2020)
Food systems practitioners are involved in a variety of activities related to local and regional food systems across the country ranging from increasing food access to developing new markets for producers. This article shares insights from two foundational courses developed by Iowa State University Extension and Outreach to support individual skill development as well as community process for strategic planning in food systems. In 2016, Local Food Leader certification was developed in Iowa to address needs for skills in equity, leadership, evaluation and facilitation. Following these workshops, and due to successful implementation of the Community Food Systems process (formerly Agricultural Urbanism Toolkit), the Food Systems team received funding through the Agricultural Marketing Resource Center to develop two certification programs: Local Food Leader (LFL) and Community Food Systems (CFS) to launch nationally. They were piloted with 14 state partners between 2018-2019 as blended delivery platforms of in-person workshops followed by online modules. Local Food Leader had a total of 429 participants and Community Food Systems had a total of 297 participants. Local Food Leader certification continued to build on its initial emphases of individual skills and Community Food Systems emphasized a process-based framework for food systems development transferable to any community to enhance their place-based food system. Multi-disciplinary audiences participated in each certification, including Land-Grant Extension agents, businesses and non-profit with the goal to provide training related to place-based development for food systems. Additionally, train-the-trainers for both certifications were developed for certified partners to offer the certifications in their own communities and create place-based capacity for development and outlets for revenue generation. This paper will review each certification and how they support food systems practitioners. It will highlight the curriculum development process, successes and challenges and evolution based on evaluation. Changes to the curriculum and new standards for teaching will be shared in hopes to provide considerations to colleagues considering new curriculum development. Last, it will detail the impact the certifications can have on community and opportunities for continuing certification work through COVID-19.
Keywords: community development; facilitation; leadership; framework; assessments; research